On the causality relationship between demographic changes, economic growth and domestic savings in Vietnam - Nguyen, Thi Thu Ha; Lam, Ba Hoa (Penerbit Universiti Kebangsaan Malaysia, 2018)
The study aims to investigate the short run and long run relationships between demographic factors (population growth and the age dependency ratio), economic growth (GDP per capita growth) and domestic savings in Vietnam for the period of 1986 to 2016 using the cointegration and Wald tests. The findings revealed that there is a cointegration relationship between domestic savings and demographic and economic variables, while Wald test shows a unique causality trend running from population growth to domestic savings in Vietnam. The policy implications from this study suggest that the Vietnam government should focus on boosting economic growth (GDP per capita growth) through mobilizing its resources, managing fertility level between urban and rural areas and population growth in relation with growth rate of the economy. Moreover, the Vietnam government should take advantage of the golden population structure and limit the effects of the dependency ratio through offering attractive beneficial programs for the elderly and provide opportunities to increase their productivity, and thus spur savings in Vietnam.